Occurrence of Ionophores in the Danish Environment - Søren Alex Bak; Erland Björklund (MDPI AG, 2014)
Antibiotics in the environment are a potential threat to environmental ecosystems as well as human health and safety. Antibiotics are designed to have a biological effect at low doses, and the low levels detected in the environment have turned focus on the need for more research on environmental occurrence and fate, to assess the risk and requirement for future regulation. This article describes the first occurrence study of the antibiotic polyether ionophores (lasalocid, monensin, narasin, and salinomycin) in the Danish environment. Various environmental matrices (river water, sediment, and soil) have been evaluated during two different sampling campaigns carried out in July 2011 and October 2012 in an agricultural area of Zealand, Denmark. Lasalocid was not detected in any of the samples. Monensin was measured at a concentration up to 20 ng·L−1 in river water and 13 µg·kg−1 dry weight in the sediment as well as being the most frequently detected ionophore in the soil samples with concentrations up to 8 µg·kg−1 dry weight. Narasin was measured in sediment samples at 2 µg·kg−1 dry weight and in soil between 1 and 18 µg·kg−1 dry weight. Salinomycin was detected in a single soil sample at a concentration of 30 µg·kg−1 dry weight.